“On Ararat Alone, no Arc can be Rest.” Beyond Morgenthau: Jews, Social Democrats, and Jewish Social Democrats: Alliances and Solidarity During the Armenian Genocide Epoch - Adam J. Sacks (International Journal of Armenian Genocide Studies, 2015)
Of all the many elements that resound and confound as similar between the overwhelming record of historical oppression endured by the Armenians and the Jews, perhaps the most telling is the echo of silence in the wider world during their hour of greatest need. As is well known, the record of Ambassador Morgenthau is a telling counterpoint to the dismaying lack of voices raised at critical junctures. It is my intention here to profile in brief other cases of Jews, from Bernard Lazare of France to Israel Zangwill of England who voiced solidarity and even sought to forge alliance with Armenians. Particular attention will be paid to the German Social Democrats Eduard Bernstein and Hugo Haase, who seceded from their party during the war years, in part, so that they could speak out with their colleagues against the Armenian Genocide. I argue that what united these figures was their progressive inclination and embrace of a discourse of human rights which often entailed a critique of nationalism, specifically mainstream Zionism. The case of the Independent Social Democrats in Germany in particular forms an overlooked corrective to a historiography of German opposition to the Armenian Genocide that has largely focused on the voices of church activists. Before turning to these case studies that broke a silence all too pervasive on the events of the Caucasian Frontline of World War I, I would like to explore the variations and forms this silence takes.